Regional Fiscal Health: An Evaluation of the Financial Performance of Gorontalo Regency - Wahyudin Hasan; Susanti Abd Mutalib; Zubaidah Rahman; Julie Abdullah; Saprudin (Institut Bisnis dan Informatika Kesatuan, 2025)
Regional autonomy through fiscal decentralization is expected to strengthen local government capacity in managing resources independently. However, many regions remain highly dependent on central transfers, making the evaluation of fiscal performance crucial to measure independence, efficiency, and effectiveness in financial management. This study aims to evaluate the fiscal health of the Gorontalo Regency Government through an analysis of financial performance over the period 2018–2023. The research employs a descriptive quantitative approach, utilizing secondary data obtained from official government financial reports. The analysis is conducted using three key indicators: the financial independence ratio, the effectiveness ratio of locally-generated revenue, and the financial efficiency ratio. The findings reveal that the financial performance of Gorontalo Regency remains suboptimal. The financial independence ratio indicates a high level of dependence on central government transfers. The average effectiveness ratio of locally-generated revenue is 75.62%, which falls into the category of less effective, while the average financial efficiency ratio of 102.17% indicates inefficient budget utilization. These findings suggest the need for reforms in regional financial management to enhance fiscal independence, as well as the effectiveness and efficiency of budget implementation.